Cinephemera : archives, ephemeral cinema, and new screen histories in Canada - Druick, Zoë, 1969-; Cammaer, Gerda (Montreal & Kingston : McGill-Queen's University Press, 2014)
What do digital platforms mean for cinema studies in Canada? In an era when digital media are proliferating and thousands upon thousands of clips are available online, it seems counter-intuitive to say that audio-visual history is quickly disappearing. But the two processes are actually happening in tandem. Adopting a media-archaeological approach to the history of cinema, contributors to Cinephemera cover a wide range of pressing issues relating to Canadian cinema's ephemerality, including neglected or overlooked histories, the work of found footage filmmakers, questions about access and copyright, and practices of film archiving. Spurred by rapid changes to technologies of production, viewing, and preservation, this collection showcases both leading and emerging scholars grappling with the shifting meaning of cinema as an object of study. Film historians are put in conversation with experimental filmmakers and archivists to provide renewed energy for cinema studies by highlighting common interests around the materiality and circulation of films, videos, and other old media. Considering a wide range of cases from the earliest days of silent film production to the most recent initiatives in preservation, Cinephemera exposes the richness of moving image production in Canada outside the genres of feature length narrative fiction and documentary - a history that is at risk of being lost just as it is appearing. Contributors include Andrew Burke (Winnipeg), Jason Crawford (Champlain), Liz Czach (Alberta), Seth Feldman (York), Monika Kin Gagnon (Concordia), André Habib (Montreal), Randolph Jordan (SFU), Peter Lester (Brock), Scott Mackenzie (Queen's); Louis Pelletier (Montreal), Katherine Quanz (WLU), Micky Story (New College), Charles Tepperman (Calgary), Jennifer VanderBurgh (Saint Mary's), William C. Wees (McGill), Jerry White (Dalhousie), and Christine York (Concordia).
Introduction: Canadian Cinema, Ephemeral Cinema / Zoë Druick and Gerda Cammaer -- 1 Early Quebec Actualities and the Ephemeral Meaning of Moving Images in the Transitional Era / Louis Pelletier -- 2 Canada's Lost Frontier Epic: The Stillborn Saga of Policing the Plains / Peter Lester -- 3 Uncovering Canada's Amateur Film Tradition: Leslie Thatcher's Films and Contexts / Charles Teppeman -- 4 "Mental Prophylaxis": Crawley Films, McGraw-Hill Educational Films, and Orphan Cinema / Scott MacKenzie -- 5 A Thrill Every Minute!": Travel-Adventure Film Lectures in the Post-War Era / Liz Czach -- 6 "Versions, Revisions, and Adaptations": Film Production in Two Languages at the National Film Board / Christine York -- 7 Breaking New Ground: Canada's First Found-Footage Films / WIllima C. Wees -- 8 Unfinished Films and Posthumous Cinema: Charles Gagnon's R69 and Joyce Wieland's Wendy and Joyce / Monika Kin Gagnon -- 9 Tiger Child: IMAX and Donald Brittain Times Nine / Seth Feldman -- 10 Ephemeral Godard: Video, History, and Quebec / Jerry White -- 11 Out Here: Feeling Bad, Feeling Gay in Michel Audy's Luc ou la part des choses and Crever à vingt ans / Micky Storey and Jason B. Crawford -- 12 Against Ephemerality: The CBC's Archival Turn, 1989-96 / Jennifer VanderBurgh -- 13 Seeing Then, Hearing Now: Audiovisual Counterpoint at the Intersection of Dual Production Contexts in Larry Kent's Hastings Street / Randolph Jordan -- 14 Preserving Ephemeral Aboriginal Films and Videos: The Archival Practices of Vtape and ISUMATV / Katherine Quanz -- 15 Preserving/Burning: Karl Lemieux's Film Performances / André Habib -- 16 Films Collecting Dust and Dusty Film Collages: Ephemerality at Work / Gerda Cammaer -- 17 Sampling Heritage: The NFB's Digital Archive / Zoë Druick -- 18 Memory, Magnetic Tape, and Death by Popcorn: The Tragedy of the Winnipeg Jets / Andrew Burke.
Includes bibliographical references (pages 359-375) and index.
English.
Description based on online resource; title from digital title page (viewed on April 02, 2025).
eBooks on EBSCOhost
Keywords: Motion pictures -- Canada -- History; Motion pictures -- Preservation -- Canada; Motion pictures -- Canada -- Archival resources; Motion picture film -- Preservation -- Canada; Digital cinematography -- Canada; Cinéma -- Canada -- Histoire; Films (Pellicules cinématographiques) -- Conservation -- Canada; Cinéma -- Fonds d'archives -- Canada; Cinéma numérique -- Canada; Cinéma -- Canada -- Fonds d'archives.; Cinéma -- Conservation -- Canada; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion picture film -- Preservation; Digital cinematography; Motion pictures; Motion pictures -- Archival resources; Motion pictures -- Preservation; Canada; Electronic books; History